What Do I Get For My ACE Dues? - William E. Carnahan (Journal of Applied Communications, 1987)
At the 1982 ACE meeting in Biloxi, Mississippi, it was voted to raise annual dues from 25 to 45. At that time, it was estimated that each member was costing ACE about 34 in services. There was some discussion about raising the dues to 50, but it was felt doubling the dues would be too much.